The use of GIS-tools in Regional and Urban planning applied to the Águeda Region (Northern Portugal) - Duarte, Isabel (2012)
The engineering geological map of Águeda Region was completed based on the analysis and interpretation of the geological and geotechnical data obtained in studies undertaken in the region. These data have various origins, scales of acquisition and purposes. The geotechnical units were interpreted using field work, in situ tests, laboratory tests on collected samples, and the collection of information contained in geotechnical reports. The different thematic maps were treated as factors and given a variable weight for the construction of the final maps, which are a construction suitability map and a risk of flooding map. It was on this phase of processing the final map that the GIS prove to be a reliable and powerful tool. It was possible to test different scenarios and determine how the different factors impact upon the final result.